Amphiphilic Cationic Macromolecules Highly Effective Against Multi-Drug Resistant Gram-Positive Bacteria and Fungi With No Detectable Resistance - Mukherjee, Sudip; Barman, Swagatam; Mukherjee, Riya; Haldar, Jayanta (Frontiers in Bioengineering and Biotechnology, 2020)
The ever increasing threats of Gram-positive superbugs such as methicillin-resistant Staphylococcus aureus (MRSA), vancomycin-resistant Staphylococcus aureus (VRSA) and vancomycin-resistant Enterococccus faecium (VRE) are serious matter of concern worldwide towards public health. Such pathogens cause repeated recurrence of infections through the formation of biofilms which consists metabolically inactive or slow growing dormant bacterial population in vast majority. Concurrently, dispersal of biofilms originates even more virulent dispersed cells responsible for pathogenesis. Along with this, fungal infections most commonly associated with Candida albicans also created a major complicacy in human healthcare. Moreover, concomitant survival of C. albicans and MRSA in a multispecies biofilms created extremely complicated polymicrobial infections. Surprisingly, infections associated with single species biofilm as well as multiple species biofilm (co-existence of MRSA and C. albicans) are almost untreatable with conventional antibiotics. Therefore, the situation demands an urgent development of antimicrobial agent which would tackle persistent infections associated with bacteria, fungi and their biofilms. Towards this goal, herein we developed a new class of branched polyethyleneimine based amphiphilic cationic macromolecules (ACMs) bearing normal alkyl, alkyl ester and alkyl amide moieties. An optimized compound with dual activity against drug-resistant bacteria (MIC = 2-4 μg/mL) and fungi (MIC = 4-8 μg/mL) was identified with minimal toxicity towards human erythrocytes (HC50 = 270 μg/mL). The lead compound, ACM-AHex (12) displayed rapid bactericidal and fungicidal kinetics (>5 log CFU/mL reduction within 1-4h). It also killed metabolically dormant stationary (MRSA and VRE) and persister (S. aureus) cells. Moreover, this compound was able to disrupt the preformed biofilm of MRSA and reduced the bacterial burden related to the dispersed cells. It showed significant proficiencies to eliminate polymicrobial biofilms of MRSA and C. albicans. Bacteria also could not develop any resistant against this class of membrane active molecules even after 15 days of successive passages. Taken together this class of macromolecule can be developed further as a dual therapeutic agent to combat infections associated with bacterial and fungal co-existence.